EUSTAR biobanking: recommendations for the collection, storage and distribution of biospecimens in scleroderma research. Issue 7 (1st February 2011) - Beyer, Christian; Distler, Jörg H W; Allanore, Yannick; Aringer, Martin; Avouac, Jérôme; Czirják, László; Cutolo, Maurizio; Damjanov, Nemanja; Del Galdo, Francesco; Fligelstone, Kim; Guiducci, Serena; Kowal-Bielecka, Otylia; et al.
Abstract : The European League Against Rheumatism Scleroderma Trials and Research Group (EUSTAR) has established an online database with clinical data of currently more than 8200 patients with systemic sclerosis (SSc). In addition to clinical research, EUSTAR fosters biomolecular studies to develop novel biomarkers and therapies for SSc. High-quality biospecimens are the basis for successful biomolecular studies. The EUSTAR biobanking group has therefore developed recommendations to standardise the collection, storage and distribution of SSc biospecimens at EUSTAR centres. These recommendations consider the scientific challenges associated with biomolecular research in SSc and the organisational requirements of EUSTAR. They were approved by the EUSTAR executive committee as well as the EUSTAR board. Once they become effective, these recommendations will be the basis for international EUSTAR studies with large numbers of SSc biospecimens. These recommendations might also be followed by other SSc consortia to enable exchange of biosamples between different SSc initiatives and might serve as a template for biobanking initiatives in other rheumatic diseases.